Modular Ax-Lindemann-Weierstrass with Derivatives - Pila, J (2013)
In a recent paper I established an analogue of the Lindemann- Weierstrass part of Ax-Schanuel for the elliptic modular function. Here I extend this to include its first and second derivatives. A generalization is given that includes exponential and Weierstrass elliptic functions as well. © 2013 by University of Notre Dame. © 2013 by University of Notre Dame.